Hulu and Hang Understanding Viewer Sessions with Big Data - Beley, Catherine; Huff, Herbie (Data Science Salon, 2019)
Everyday, Hulu ingests 100 terabytes of user level app interaction data. This session data is the closest touchpoint we have to subscribers' experience in our product short of joining them on their couch in their living rooms. Making meaning out of session data is a non-trivial effort across data instrumentation, engineering, analytics, and data science teams. In this talk, you will get an inside look at how we are tackling this monumental project at Hulu: from product design, to generating insights, to building predictive models - all to create the most personalized and engaging streaming experience for our subscribers.
Online resource; Title from title screen (viewed September 10, 2019)
Keywords: Hulu; Consumer satisfaction; Streaming technology (Telecommunications); Big data; Consommateurs; Satisfaction; En continu (Télécommunications); Données volumineuses; Electronic videos